2008
DOI: 10.1084/jem.20080238
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive CD40 signaling in B cells selectively activates the noncanonical NF-κB pathway and promotes lymphomagenesis

Abstract: CD40, a member of the tumor necrosis factor (TNF) receptor family, plays an essential role in T cell–dependent immune responses. Because CD40 is widely expressed on the surface of tumor cells in various B cell malignancies, deregulated CD40 signaling has been suggested to contribute to lymphomagenesis. In this study, we show that B cell-specific expression of a constitutively active CD40 receptor, in the form of a latent membrane protein 1 (LMP1)/CD40 chimeric protein, promoted an increase in the number of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
145
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 49 publications
(46 reference statements)
4
145
0
Order By: Relevance
“…Finally, by investigating ex vivo LN samples, we show that the relevant signaling pathways and antiapoptotic Bcl-2 family members are active factors in these proliferation centers. It is known that constitutive CD40 signaling in murine B cells induces alternative NF-kB activation and promotes lymphomagenesis (Homig-Holzel et al, 2008). This correlates well with our finding that prolonged CD40L stimulation of CLL cells (24-72 h) resulted in alternative NF-kB activation and upregulation of Bcl-X L levels.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, by investigating ex vivo LN samples, we show that the relevant signaling pathways and antiapoptotic Bcl-2 family members are active factors in these proliferation centers. It is known that constitutive CD40 signaling in murine B cells induces alternative NF-kB activation and promotes lymphomagenesis (Homig-Holzel et al, 2008). This correlates well with our finding that prolonged CD40L stimulation of CLL cells (24-72 h) resulted in alternative NF-kB activation and upregulation of Bcl-X L levels.…”
Section: Discussionsupporting
confidence: 91%
“…By analyzing immunized CD40LTg mice, we demonstrated that GCs grow only up to day 5 in these mice, followed by rapid regression. Early regression of GCs by CD40 signaling is consistent with the previous observation that GC formation is ablated by stimulation with agonistic anti-CD40 Ab or constitutive CD40 signaling (14,17). Although previous studies did not examine the early GC responses, we demonstrated that generation of early GCs up to day 5 is not defective in CD40LTg mice and presented evidence strongly suggesting that early GCs in CD40LTg mice are functional.…”
Section: Discussionsupporting
confidence: 79%
“…To assess in vivo immunological function of CD40L on B cells, we established CD40L transgenic (CD40LTg) mice that constitutively express CD40L on B cells and demonstrated that CD40LTg mice spontaneously develop SLE-like autoimmune disease (13), suggesting that constitutive CD40L expression on B cells has a role in the development of SLE. Recently, Hömig-Hölzel et al (14) established transgenic mice that express EBV latent protein membrane 1/CD40 chimera on B cells that generates constitutive CD40 signaling and demonstrated that these mice develop B cell lymphomas. Thus, CD40 signaling seems to play a crucial role in autoimmunity and leukemogenesis, as well as normal immune responses.…”
mentioning
confidence: 99%
“…The heightened activation state caused by LMP1 expression in mice leads to B-cell hyperactivity, resulting in splenomegaly, lymphadenopathy, and production of elevated serum IL-6 and autoantibodies (4). The amplified and constitutive CD40-like signal provided by LMP1 can also contribute to generation of Reed-Sternberg cells (8) and B-cell lymphoma (9).…”
mentioning
confidence: 99%